Perceived police fairness: exploring the determinants of citizens’ perceptions of procedural fairness in Ghana - Boateng, Francis D. (Policing and society, 2020)
The purpose of this study is to examine factors affecting citizens’ perceptions of police procedural fairness. More specifically, using data systematically collected from two large metropolitan areas in Ghana, the current study examines the independent contributions of three categories of factors - demographic factors, attitudinal factors, and experiential factors - on perceptions of fairness. An ordinal regression analysis conducted to assess the predictive effects of these variables indicates that citizens’ assessments of police fairness are largely driven by their experiences with the police, views about police effectiveness, levels of trust in the police, and their own individual characteristics. These observations are noteworthy, and provide a platform for future research, policy formation, and continued debate about the utility of the procedural justice theory in policing.